ANALISIS KESTABILAN MODEL DUA PEMANGSA DAN SATU MANGSA DENGAN PENERAPAN RACUN - Irham Taufiq (Universitas Sarjanawiyata Tamansiswa, 2016)
This research discussed prey and predator model showing the interaction between one prey and two predators by using poison. The interaction between prey and predator used response function of Holling type II. The growth of prey and predator used logistic function. From the model, it was found five equilibrium points. The local stability of each equilibrium point was analyzed. To make it easier in interpreting the dynamic between prey and two predators and the effect of giving poison, the numeric simulation was done by showing the change of parameter of the level of death due to poison and the efficiency of changing the prey consumption towards the birth of the first and second predators